LEGAL PLURALISM IN EARLY MODERN ENGLAND - Birch, Dominic (REI - REVISTA ESTUDOS INSTITUCIONAIS, 2019)
This article argues that early modern England should be considered as a legally pluralistic society. Historians have long recognised the fact of early modern legal pluralism, however few use this term and discussion of what this might mean is absent from the historiography. This article seeks to integrate the theory behind legal pluralism with the study of early modern England. Furthermore, this article argues that bringing the early modern into the study of legal pluralism adds historical depth to the concept, and allows legal pluralists to consider a pluralism that was state-endorsed, rather than oppositional to the state.